Overcoming resistance and resilience of an invaded community is necessary for effective restoration: a multi-site bracken control study - Alday, Josu G.; Cox, Emma S.; Pakeman, Robin J.; Harris, Mike P. K.; Le Duc, Mike G.; Marrs, Rob H. (The Journal of applied ecology, 2013)
1. The search for appropriate management strategies to control invasive plants is an important theme in environmental management. However, the recovery of the resident community species complement does not necessarily respond predictably to restoration efforts. Increasing restoration success requires an understanding of the resistance and resilience of the invaded community and the response of the newly developing community to management. Here, we used Pteridium-invaded heath and grass communities as a test system and investigated the effects of recommended Pteridium aquilinum control treatments on vegetation composition and diversity. 2. We evaluated seven field experiments in four regions of Great Britain designed to test five Pteridium control treatments, including 'one-off' (applied only at the start) and 'repeated' (applied regularly) treatments, against an untreated experimental control. The sites had context-dependent restoration targets, either a Calluna heathland or acid grassland. Species cover and diversity responses (higher plants, mosses plus lichens) to these treatments were monitored annually for 10 years. 3. Pteridium control treatments induced significant change in species composition compared to experimental controls in both vegetation types. On Calluna target sites, 'repeated' treatments overcame the resistance of the invaded community producing a gradual divergence in species composition and species diversity. In contrast, the 'one-off' treatments were ineffective. 4. At the acid grassland target sites, all treatments overcame the resistance of the Pteridium-dominated state producing changes in species composition in comparison with experimental controls. 5. Synthesis and applications. There are two important results for land managers: (i) where Calluna heathland is the target, 'repeated' treatments (cutting once or twice per year) were effective in overcoming the resistance of invaded community and moving species composition towards the target state, effectively creating an alternative state; (ii) where acid grassland is the target both 'one-off' and 'repeated' treatments overcame the invaded community resistance ('one-off' also overcame resilience) producing changes in species composition in the desired direction. The effectiveness of 'one-off' treatments was site dependent and produced alternative stable states within 10 years. In contrast, 'repeated' treatments were site independent but took longer to work and were more expensive.